Hijaukan Harapan: Tumbuhan Obat sebagai Pilar Resiliensi dan Kemandirian Ekonomi Masyarakat - Kaho, Uly J. Riwu; Jhon Liem; Ferdinand Lopo; Naisanu, Joritha; Henny A. Raga (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The use of medicinal plants plays a crucial role in enhancing community resilience, particularly in maintaining health and strengthening economic independence. This community service activity was conducted in Tuatuka Village, Kupang Regency, on July 31, 2025. The program aimed to improve community knowledge and skills in identifying, cultivating, and processing medicinal plants into economically valuable products. The methods used included outreach, practical training in herbal product production, and mentoring of small business groups. The results of the activity demonstrated an increased community understanding of the benefits of medicinal plants, the formation of herbal product promotion groups, and community enthusiasm in developing medicinal plant-based businesses. Support from the village government also strengthened the program's sustainability. With a participatory approach, this activity successfully mobilized local potential as a sustainable health and economic solution. This activity is expected to become a model for community empowerment in managing natural resources for shared resilience and prosperity.